Identification and quantification of erosion on a sand tailings dam. Issue 3 (3rd May 2020) - Slingerland, N.; Sommerville, A.; O'Leary, D.; Beier, N.A.
ABSTRACT: The Athabasca oil sands (AOS) mining region is home to some of the largest sand tailings dams on earth. Each of these is expected to be converted to stable landforms, delicensed as dams, and reclaimed. This project sought to identify, quantify, determine cause of erosion on an active sand tailings dam in the AOS, and to quantify the soil loss using remote techniques that might be used in monitoring long-term performance. Light Detection and Ranging (LiDAR) data were assessed in the form of 1-m contours, and digital stereo aerial photography was viewed in three dimensions at scales of 1:750 or greater using PurVIEW and ArcGIS softwares. Water and wind erosion were found to be altering the tailings dams. Over 190 gullies and earth flows were identified, causing an estimated loss of over 14, 800 m 3 of sand tailings: a substantial sum considering the regular maintenance the dams receive. Both LiDAR data and digital stereo aerial photography are shown to deliver different, yet essential, performance information for use throughout post-closure monitoring phases. These tools provide a safe and efficient approach for regulators and dam owners to monitor, assess, and quantify tailings dam/landform performance such that decisions may be made systematically regarding reclamation certification.